DOMESTIC VIOLENCE AND ITS IMPACT ON THE EDUCATION OF THE NIGERIAN CHILDREN - Lawal, Suleiman; Ishaq, Ismail Jaf’afar (Sokoto Educational Review, 2011)
The paper examined domestic violence and its impact on the education of Nigerian children. Violence was defined in the paper as the exercise of power which can be active (injury), passive (i.e. neglect) or deprivation, intentional or negligent. The concept of domestic violence was discussed in the paper by looking at its typology; which includes physical abuse, emotional abuse and psychological abuse, its symptoms are; agitation, anxiety, regressed behaviour, withdrawal and sleeping difficulty and its causes include; use of drug, alcohol and anger. The impact of domestic violence on Nigerian children is highlighted under three perspectives: cognitive effects, emotional effects, and behavioural and social effects. The paper was concluded by stating that domestic violence disrupts children’s concentration in school task, school adaptation and academic success and finally, it was recommended that teachers should be equipped with skills of identifying children that are emotionally, cognitively, behaviorally and socially affected by domestic violence and find ways of solving their problems.